Over twenty years of publications in Ecology: Over-contribution of women reveals a new dimension of gender bias - Fontanarrosa, Gabriela; Zarbá, Lucía; Aschero, Valeria; Dos Santos, Daniel Andrés; Núñez Montellano, María Gabriela; Plaza Behr, Maia C.; Schroeder, Natalia; Lomáscolo, Silvia Beatriz; Fanjul, María Elisa; Monmany Garzia, A. Carolina; Alvarez, Marisa; Novillo, Agustina; et al. (Plos ONE, 2025)
Biographical features like social and economic status, ethnicity, sexuality, care roles, and gender unfairly disadvantage individuals within academia. Authorship patterns should reflect the social dimension behind the publishing process and co-authorship dynamics. To detect potential gender biases in the authorship of papers and examine the extent of women’s contribution in terms of the substantial volume of scientific production in Ecology, we surveyed papers from the top-ranked journal Ecology from 1999 to 2021. We developed a Women’s Contribution Index (WCI) to measure gender-based individual contributions. Considering gender, allocation in the author list, and the total number of authors, the WCI calculates the sum of each woman’s contribution per paper. We compared the WCI with women’s expected contributions in a non-gender-biased scenario. Overall, women account for 30% of authors of Ecology, yet their contribution to papers is higher than expected by chance (i.e., over-contribution). Additionally, by comparing the WCI with an equivalent Men’s Contribution Index, we found that women consistently have higher contributions compared to men. We also observed a temporal trend of increasing women’s authorship and mixed-gender papers. This suggests some progress in addressing gender bias in the field of ecology. However, we emphasize the need for a better understanding of the pattern of over-contribution, which may partially stem from the phenomenon of over-compensation. In this context, women might need to outperform men to be perceived and evaluated as equals. The WCI provides a valuable tool for quantifying individual contributions and understanding gender biases in academic publishing. Moreover, the index could be customized to suit the specific question of interest. It serves to uncover a previously non-quantified type of bias (over-contribution) that, we argue, is the response to the inequitable structure of the scientific system, leading to differences in the roles of individuals within a scientific publishing team.